Experiences Gained during the Development of a Passive BSAR with GNSS Transmitters of Opportunity. (12th June 2008) - Cherniakov, M.; Saini, Rajesh; Antoniou, Michael; Zuo, Rui; Plakidis, Eleftherios
Abstract : This paper presents an overview of the research conducted at University of Birmingham. It highlights and briefly discusses various systems parameters (e.g., resolution, power budget), problems (e.g., interference, heterodyne channel Doppler compensation), and signal processing algorithms (imaging, synchronization) required for successfully obtaining an image. The GLONASS satellite is used for experiential confirmation of the main results. All these results are presented and briefly discussed.